Improved antimutagenic effect of Pyrostegia venusta (Ker Gawl.) Miers nanostructured extract in liposome and polymeric nanoparticle - Patrícia Zanco; Stela Regina Ferrarini; Letícia Cruz; Luana Mota Ferreira; Rogério de Campos Bicudo; Larissa Cavalheiro; Gerardo Magela Vieira Júnior; Marina Mariko Sugui (Brazilian Journal of Pharmaceutical Sciences, 2022)
Abstract Pyrostegia venusta (Ker Gawl.) Miers, popularly known as “Cipó-de São-João”, has been used in traditional medicine for its therapeutic properties. Nanotechnology is able to enhance the pharmacological activity of plant extracts. In this context, liposomes and polymeric nanoparticles containing P. venusta ethanolic extract were developed and then physico-chemically characterized to evaluate the mutagenic/antimutagenic effects of P. venusta. In addition, transaminases and serum creatinine were biochemically analyzed for liver and renal damage, respectively. The micronucleus test was performed with male Swiss mice treated orally for 15 consecutive days with free extracts and nanostructured with P. venusta, and then intraperitoneally with N-ethyl-N-nitrosurea (50 mg/kg) on the 15th day of treatment. Micronucleated polychromatic erythrocytes (MNPCE) were evaluated in bone marrow. There was a significant reduction in the frequency of MNPCE (LPEPV = 183% and NPEPV = 114%, p < 0.001), indicating antimutagenic potential of the nanostructured extracts with P. venusta. The groups treated with only nanostructured extract did not show an increase in MNPCE frequency, and biochemical analyzes showed no significant difference between treatments. The liposomes and polymeric nanoparticles containing Pyrostegia venusta ethanolic extract showed biological potential in preventing the first step of carcinogenesis under the experimental conditions.